The potential use of plant species within a Renosterveld landscape for the phytoremediation of glyphosate and fertiliser - DM Jacklin; IC Brink; J de Waal (Water SA, 2020)
In South Africa, fertiliser and herbicide pollutants resulting from agricultural practices indirectly lead to the degradation of surface freshwater and groundwater quality. Nitrogen and phosphorus, and glyphosate, derived from agricultural fertiliser and herbicide applications, respectively, contribute to watercourse toxicity. Adjacent to many of the surface freshwater systems are some of South Africa’s most productive agricultural lands, where natural ecosystems are converted to croplands, resulting in the degradation of natural vegetation and deterioration of freshwater quality. The critically endangered status of some Renosterveld vegetation types is the product of agricultural expansion, nutrient loading through fertilisation and the spraying of herbicides. A buffer of Renosterveld vegetation along river corridors may contribute to the remediation of agricultural pollutants prior to entering watercourses. The utilisation of wetland plants occurring within Renosterveld for agricultural pollutant extraction can increase river corridor biodiversity, creating indigenous refuges and facilitating habitat connectivity. A laboratory phytoremediation system was designed and constructed to investigate the pollutant-removal potential of indigenous species occurring in Renosterveld vegetation (amongst other areas), compared with commonly used invasive alien plants (IAP) in floating wetland designs. Five pollutant parameters – ammonia, nitrate, orthophosphate and two glyphosate concentrations – reflect environmental stresses on 14 wetland species naturally occurring within Renosterveld vegetation. Effluent analyses indicated significant removal efficiencies for the indigenous vegetation across both fertiliser and herbicide pollutants, with the two most effective species identified as Phragmites australis and Cyperus textilis, with 95.87% and 96.42% removal, respectively. All wetland species displayed greater pollutant removal than the unvegetated soil control and when compared to an IAP and palmiet assemblage, indicated similar pollutant-removal efficiencies, justifying their use as an acceptable alternative.